A modeling approach for the development of process driven web applications - Mubin, Siti Azreena; Jantan, Azrul Hazri (ESRSA Publications, 2014)
Complex web applications have been developed rapidly as to support complex process and transactional workflows involved in the web domain. Although there are numerous modeling concepts exist in web applications nowadays, new issues raises in modeling approach such as user interactions, interrelated process flow, navigational issues and graphical user interface concerns. In this paper, we present and discuss user interaction diagram, Unified Modeling Language (UML) notation and object-oriented approach for necessity in complex web applications. A proposed model called UEWDM (UML-Extensions Web Design Model) emphasize on the user interaction issues as well as the interrelated process, navigation and graphical user interface. The uniqueness of UEWDM is in the design pattern modeling approaches. At the end of the paper, future works of the design model will be explained and briefly summarized.